Derivative activities and Chinese banks' exposures to exchange rate and interest rate movements. Issue 7 (15th July 2017) - Adcock, Chris; Hua, Xiuping; Mazouz, Khelifa; Yin, Shuxing
Abstract : This study investigates the impact of Chinese banks' derivative activities on their exposure to exchange rate and interest rate changes. The standard Jorion [1990. "The Exchange-Rate Exposure of U.S. Multinationals." Journal of Business 63 (3): 331–345] model provides weak evidence of Chinese banks' exposure to these risks. However, the exposure increases substantially when time-varying exposure regressions with orthogonalised market returns are used. We also show that Chinese banks exhibit linear and nonlinear exposures to the exchange rate and interest rate fluctuations. Further analysis indicates that the use of derivatives reduces banks' foreign exchange risk, but does not affect their interest rate exposure. Derivative products are more likely to be used as an integrated part of the Chinese banks' risk management systems, which could thus help to stabilise the banking system.